Analytical investigation of well/perforation scale effect on sand production of weakly consolidated sandstones - Tehrani, S.; Sarmadivaleh, Mohammad; Sinaki, Y.; Mostofi, Masood; Bayati, Massoud (Media Dynamics, 2016)
Investigating the risk of sand production is a common practice for developing unconsolidated and weakly consolidated reservoirs, particularly with designing the completion system of development wells. The risk of sanding may be different for open hole and cased and perforated completion systems. Part of this difference is a result of the different size of the boreholes—that is, open hole versus perforation tunnels— which is known as borehole scale effect. The amount of research dedicated to investigate the borehole scale effect on sand production is very limited. Research has been carried out by conducting thick-walled cylinder (TWC) tests on samples with different inner to outer diameter ratios. The impacts of sample size and boundaries on the induced stresses around the borehole and failure were, however, not differentiated from the borehole scale effect. In this paper, a comprehensive analytical approach is performed to investigate the effect of the size of the sample and boundaries on TWC tests and borehole failure. To do this, four different failure criteria—Mohr-Coulomb, Drucker-Prager, Mogi and modified Lade—are compared with previously published experimental results. The analysis shows that the size of the sample and the boundaries may significantly change the TWC strength of the rock. The TWC changes by different inner to outer diameter ratios, however, may not be fully justified by the analytical approach. Hence, a scale effect factor must be introduced to replicate the experimental results.